Advanced Chemical Methods for Stereoselective Sialylation and Their Applications in Sialoglycan Syntheses. Issue 11 (24th May 2021) - Vibhute, Amol M.; Komura, Naoko; Tanaka, Hide‐Nori; Imamura, Akihiro; Ando, Hiromune
Abstract: Sialic acid is an important component of cell surface glycans, which are responsible for many vital body functions and should therefore be thoroughly studied to understand their biological roles and association with disorders. The difficulty of isolating large quantities of homogenous‐state sialoglycans from natural sources has inspired the development of the corresponding chemical synthesis methods affording acceptable purities, yields, and amounts. However, the related syntheses are challenging because of the difficulties in α‐glycosylation of sialic acid, which arises from its certain structural features such as the absence of a stereodirecting group at the C3 position and presence of carboxyl group at the anomeric position. Moreover, the structural complexities of sialoglycans with diverse numbers and locations of sialic acid on the glycan chains pose additional barriers. Thus, efficient α‐stereoselective routes to sialosides remain highly sought after, although various types of sialyl donors/acceptors have been developed for the straightforward synthesis of α‐sialosides. Herein, we review the latest progress in the α‐stereoselective synthesis of sialosides and their applications in the preparation of gangliosides and other sialoglycans. Abstract : Sialic acid Chemistry : Chemical methods for stereoselective α‐sialylation serves as an invaluable tools to obtain the highly complex sialoglycans and fluorescent probes for the glycobiological studies. This review highlights the step‐by‐step progress from the initial moderate to the recent fully α‐ stereoselective sialylation methods by using macrobicyclic sialyl donors followed by their applications in sialoglycans/probes synthesis.